RANCANG BANGUN SISTEM INFORMASI PENERIMAAN SISWA BARU DENGAN FITUR E-REMINDER BERBASIS WHATSAPP GATEWAY : STUDI KASUS SDIT RABBANI KOTA BENGKULU - Suryamen, Haris; Wahyuni, Ullya Mega; Aziz, Muhammad Fairuzi Iszam (ITP Press, 2025)
In the ever-evolving digital era, managing data and information in educational environments has become increasingly crucial. The new student admission process at SDIT Rabbani Kota Bengkulu still faces several challenges, such as document accumulation, difficulties in data management, and delays in administrative procedures. These issues hinder the smooth and efficient execution of the admission process. To address these problems, this study aims to design and develop a web-based student admission information system equipped with an e-Reminder feature through a WhatsApp Gateway. The research adopts the Waterfall development methodology, which includes analysis, design, implementation, testing, and maintenance stages. The system is built using the Laravel and Vue.js frameworks and is integrated with WhatsApp services to send automatic notifications regarding important admission steps and schedules. The implementation results indicate that the system has successfully streamlined the admission process, reduced administrative delays, and improved communication between the school and prospective student guardians. Therefore, this system enhances administrative performance in student admissions and provides a more modern and informative service experience.